Adaptation of Wayame village Agriculture in Climate Change Through Innovative CSR Programs with The SDGs Approach - Ika Bayu Kartikasari; Paulus Oberto; Muhamad Jauhari; Dyah Ayu Pujiatikinasih (Publisher Cv. Inara, 2020)
Climate change is a phenomenon of erratic weather changes caused by conditions of temperature and rainfall. Based on this phenomenon, agriculture is the sector that has the most impact on climate change due to decreased productivity of food crops. This can be seen from the increasing number of pests and plant diseases being planted. If this problem continues, the economic income of the farmers will decline and tend to experience a food crisis. Therefore, Pertamina MOR VIII entered the community by overcoming problems that occurred through the CSR program. The CSR program carried out by the Kranjang Hamlet farmer group is based on climate change conditions and the SDGs concept. In the agricultural sector, there are several SDGs indicators that intersect, such as freedom from hunger, a healthy and prosperous life, the need for clean water, and the handling of climate change. Kranjang Hamlet, which is located in Wayame Village, is a hamlet located in the Ambon Islands District which is vulnerable to climate change. Because of this vulnerability, Adaptation is carried out to answer problems that occur in the village. By looking at some of these problems, the purpose of this study is to determine (1) community behavior in facing climate change, (2) CSR programs regarding climate change adaptation, and (3) Application of community CSR programs based on SDGs. The results of the research found were (1) The community's knowledge regarding climate change was relatively low, (2) The realization of the achievement of SDGs 1 in responding to community needs, especially for farmer groups (3) To achieve SDGs 2, the Company has provided training to improve community adaptation to climate change such as goat livestock as a substitute for non-organic fertilizers, training in composting from livestock manure, and training in the prevention of agricultural diseases or pests organized by the company. (4) In achieving SDGs 3 and SDGs 6, it is done by making hydram pumps to irrigate agriculture and the community's need for clean water. The conclusion of this study is that the company has provided a CSR program to the people of Wayame Village to meet the needs of the Village farmer groups. So that the community has the capacity to see and understand the climate change adaptation process in the agricultural sector in Wayame Village.